The characteristics of the optimal beneficiary population for robotic⁃assisted radical resection of colorectal cancer - LI Hang*，GU Haitao，LI Dongxue，XIAO Minfeng (Zhongguo linchuang yanjiu)
Objective To compare the impact of robotic-assisted versus laparoscopic-assisted radical resection for colorectal cancer on perioperative outcomes using propensity score matching（PSM），and to explore the optimal patient population for robotic surgery during its initial and intermediate stages of implementation. Methods A retrospective analysis was conducted on patients who underwent radical resection for colorectal cancer at the Second Affiliated Hospital of Chongqing Medical University from January 2022 to December 2023. PSM was performed based on patients' sex，age，body mass index（BMI）， and surgical site. The primary outcomes were short-term postoperative results（reoperation rate，time to first flatus，time to first liquid intake，postoperative hospital stay，and total hospital stay）in the matched cohort. Secondary outcomes included intraoperative conditions（operation duration，estimated blood loss，intraoperative transfusion rate，conversion to open surgery，and number of lymph nodes dissected）and postoperative infectious complication rates.Results A total of 1 031 patients were included. After 1∶1 PSM between the robotic group （n= 147）and the laparoscopic group（n=884），142 matched pairs were retained. In the matched cohort，the laparoscopic group had a shorter operation time than the robotic group［179.48（69.88）min vs 237.98（82.27）min，U=6.849，P<0.01］. Significant differences were observed between the robotic and laparoscopic groups in estimated blood loss［50（20）mL vs 50（30）mL，U=2.746，P=0.006］，time to first liquid intake［（3.86±1.87）d vs（4.27±1.70）d，t=2.194，P=0.028］， time to first flatus［2.0（1.0）d vs 3.0（1.0）d，U=2.022，P=0.043］，postoperative hospital stay［9.5（2.0）d vs 10.0（4.0）d， U=2.790，P=0.005］，total hospital stay［14.0（4.0）d vs 15.0（6.0）d，U=2.574，P=0.010］，and infectious complication rates（11.3% vs 23.2%，P=0.008）. No significant differences were found in intraoperative transfusion rates，conversion to open surgery，number of lymph nodes harvested，or reoperation rates（P>0.05）. Subgroup analysis indicated that patients aged <65 years，female，with a BMI of 18.5 to 23.9 kg/m2，and those undergoing radical rectal resection were the optimal beneficiaries of robotic surgery.Conclusion Robotic surgery demonstrates advantages over laparoscopic surgery in postoperative recovery and infectious complication rates. Surgeons in the early and intermediate stages of robotic surgery adoption may prioritize patients aged <65 years，female，and with a BMI of 18.5 to 23.9 kg/m2 for robotic-assisted procedures.